Obama's War: A Lecture - Ali, Tariq (Social justice, 2010)
The article presents a speech by Tariq Ali, a military historian and commentator, delivered in London, England and broadcast in the U.S. on April 19, 2010. Topics discussed include the military strategy of the U.S. in the Afghan war, U.S. support of Afghan President Hamid Karzai, and predictions for the outcome of the war. An interview with Ali is also included on topics such as the foreign policy of U.S. President Barack Obama.